Self-Adjustment and Social Conflict of Multicultural Students - Arlia Yulfi Susanti; A Muri Yusuf; Firman Firman (Universitas Negeri Padang, 2019)
Social conflict became one of the phenomena commonly found in schools. To avoid conflict, good adjustment is needed. Meanwhile there are still many multi-ethnic students who have difficulty adjusting themselves to cause conflicts such as fights, disputes and debates that lead to violence. The aim is to find out the picture of adjustment and social conflict experienced by students and to know the relationship between adjustment and social conflict experienced by students. The research sample consisted of 104 students with Stratified Random Sampling. The instrument used was a questionnaire about adjusting the Likert Scale model with a reliability of 0.724 and a questionnaire about social conflict at 0.727. The results showed that there was a significant negative relationship between adjustment and social conflict experienced by students (r = -0.582). If the adjustment of students is getting better, the social conflicts experienced by students will decrease and vice versa. It means that some of the multi-ethnic students experience social conflict and counseling services are needed to resolve the conflict.